Batu Bata Merah Ramah Lingkungan Menggunakan Bahan Campuran Abu Serbuk Kayu dan Serbuk Kaca - Irwinsyah Aprillio Putra Pratama; Naufal Bagus Setiawan; Bambang Setiabudi; Shifa Fauziyah (Universitas Diponegoro, 2024)
Along with the times in the Industrial Revolution 4.0, innovation in the construction field is needed to achieve a specific innovative idea. One is making red bricks using a mixture of ash, sawdust, and glass powder. For the composition used in red bricks with a mixture of ash, sawdust, and glass powder amounting to 0%, and 2.5% and 0%, 2.5%, 5%, and 7.5% of the weight of the bricks used, based on these percentages, it can also reduce the price of production materials. The researchers did the test method by testing the brick's compressive strength and the absorbency of water. This aims to find out how significant the influence of the mixture of ash, sawdust, and glass powder is on the quality of the brick's compressive strength and the level of water absorption in the brick. It is hoped that the research of red bricks using a mixture of ash, sawdust, and glass powder is expected to be an alternative solution for the utilization of red brick mixture materials to reduce the cost efficiency of production materials and to determine the quality results of brick compressive strength and water responsiveness to bricks based on the test method to be carried out.